Adsorption desulfurization catalyst and its preparation method and application

By using adsorption and desulfurization catalysts prepared by materials such as large pore SB powder and modified kaolin, the problems of low desulfurization efficiency of heavy oil and easy catalyst deactivation in the prior art are solved, and efficient desulfurization of heavy oil and long-life use of catalysts are achieved.

CN116408104BActive Publication Date: 2025-04-01PETROCHINA CO LTD
View PDF 22 Cites 0 Cited by

Patent Information

Application Number
CN202111646209.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-04-01
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

The existing desulfurizers are inefficient in the desulfurization treatment of heavy oils and are prone to inactivation, making it difficult to meet the strict restrictions on the sulfur content of marine fuel oils by the International Maritime Organization.

Method used

Adsorption and desulfurization catalysts composed of macroporous SB powder, modified kaolin, zirconium oxide, zinc, nickel, potassium, magnesium and palladium are used to adsorb the sulfur components in the oil in the form of metal sulfides such as zinc sulfide, thereby improving the desulfurization efficiency and the stability of the catalyst.

Benefits of technology

The desulfurization rate of heavy oil is significantly improved to reach more than 90%, extending the service life of the catalyst, reducing the viscosity of the oil products, and improving the quality of the oil products after desulfurization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003443936580000251
    Figure BDA0003443936580000251
  • Figure HDA0003443936590000011
    Figure HDA0003443936590000011
  • Figure HDA0003443936590000021
    Figure HDA0003443936590000021
Patent Text Reader

Abstract

The present invention provides an adsorption desulfurization catalyst and a preparation method and application thereof, wherein the adsorption desulfurization catalyst comprises a carrier, a first metal component, a second metal component and a third metal component; wherein the carrier is compounded from raw materials containing macroporous SB powder, modified kaolin and zirconium oxide, the pore volume of the macroporous SB powder is not less than 1 mL / g, and the modified kaolin is prepared according to a process comprising the following steps: the kaolin raw material is once calcined at 500°C to 700°C, then acid-modified, then washed to neutrality, and then calcined twice at 500°C to 600°C to obtain the modified kaolin; the first metal component comprises zinc and nickel, the second metal component comprises potassium and / or magnesium, and the third metal component comprises palladium. The adsorption desulfurization catalyst of the present invention has the advantages of high strength, good stability and high desulfurization efficiency, and is particularly suitable for the desulfurization treatment of heavy oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides an adsorption desulfurization catalyst and a preparation method and application thereof, belonging to the field of oil product desulfurization treatment. Background Art

[0002] Heavy oil and other oil products contain sulfides, which will cause environmental pollution and other problems. Therefore, desulfurization treatment is of great significance for the practical application of heavy oil and other oil products. For example, with the development of global trade, the consumption of marine fuel oil is increasing year by year. At present, the global demand for marine fuel oil exceeds 200 million t / a. Marine fuel oil is mainly made of atmospheric residue oil, vacuum residue oil, cracking residue oil, catalytic diesel oil and other raw materials in the crude oil processing process. The products of complete combustion are mainly carbon oxides, nitrogen oxides and sulfides. Among them, sulfides not only seriously endanger human health, but also cause acid rain. A series of serious environmental problems such as photochemical smog, therefore, reducing the sulfur content in marine fuel oil is crucial to the control of atmospheric pollutant emissions. The International Maritime Organization (IMO) announced that the new sulfur emission limit regulations will be enforced from January 1, 2020. The sulfur content of marine fuel oil worldwide will be reduced from no more than 3.5wt% to no more than 0.5wt%. Using relatively low-cost desulfurization methods to minimize the sulfur content of blending components such as light and heavy oils is an effective way to increase the output and quality of products such as fuel oil.

[0003] Hydrofining and adsorption desulfurization are common means to achieve the purpose of reducing olefins and desulfurization of oil products. For example, patent document CN104415797A discloses a pyrolysis gasoline selective hydrogenation catalyst and its preparation method and application, which are used for selective hydrogenation and removal of diolefins from cracked gasoline, but are not suitable for desulfurization of heavy oil; CN101491764A discloses a residual oil hydrogenation catalyst, which is used for the treatment of residual oil hydrodemetallization, hydrodesulfurization, hydroresidual carbon removal and hydroconversion; CN101439288A discloses a combination of Alumina-based selective hydrodesulfurization catalyst and a preparation method thereof are used for selective hydrodesulfurization of gasoline; CN105582940A discloses a desulfurization catalyst and a preparation method thereof and a method for desulfurizing hydrocarbon oil; CN104560123A discloses an adsorption desulfurization method, which contacts and reacts sulfur-containing hydrocarbon oil, a hydrogen donor, a desulfurization adsorbent and an adsorption desulfurization aid, wherein the sulfur-containing hydrocarbon oil is selected from dry gas, liquefied gas, gasoline, kerosene, diesel or gas oil, that is, the adsorbent is used for desulfurization of light gasoline; CN10 3642520A discloses a preparation and application method of an adsorption desulfurizer for catalytic cracking gasoline modification, which first prepares a ZnO / ZSM-5 core-shell structure composite material, then mixes the composite material with lithium hydroxide dry glue powder and diatomaceous earth, adds an acidic peptizing solvent solution, and then extrudes and bakes them in sequence to obtain a core-shell ZnO / ZSM-5 adsorption desulfurizer, which is used for modifying catalytic cracking gasoline with a sulfur content of less than 150ppm; CN107159096A discloses a Catalytic cracking gasoline adsorption desulfurizer and its preparation and application, used for adsorption desulfurization of catalytic cracking gasoline; CN101134908A discloses a method for non-hydrogen catalytic adsorption desulfurization of hydrocarbon oil in a moving bed reactor, which is to introduce sulfur-containing hydrocarbon oil raw material and fluidized medium into the moving bed reactor, and alternately contact with the interval-filled sulfur conversion agent and sulfur adsorbent in turn, the sulfur-containing hydrocarbon oil raw material is selected from gasoline, kerosene, diesel, and gas oil fractions, and the method uses the sulfur conversion agent and the sulfur adsorbent in combination to achieve desulfurization treatment of the above hydrocarbon oil raw material.

[0004] Desulfurizer is an important factor affecting the desulfurization effect. Optimizing the structure and performance of desulfurizer is an effective means to improve the desulfurization effect. Although there have been studies and reports on desulfurizers such as hydrodesulfurizers and adsorption desulfurizers, on the one hand, the strength, desulfurization activity, stability and desulfurization efficiency of desulfurizers at this stage need to be further improved. On the other hand, the current desulfurizers are mostly used for the desulfurization of light oils such as gasoline, kerosene and diesel, but have limited desulfurization effects on heavy oils. It is urgent to develop effective desulfurizers suitable for the desulfurization of heavy oils. Summary of the invention

[0005] The present invention provides an adsorption desulfurization catalyst and a preparation method and application thereof, which has the advantages of high catalyst strength, good stability and high desulfurization efficiency, and is particularly suitable for desulfurization treatment of heavy oil, effectively overcoming the defects of the prior art.

[0006] In one aspect of the present invention, an adsorptive desulfurization catalyst is provided, comprising a carrier, a first metal component, a second metal component and a third metal component; wherein the carrier is compounded from raw materials containing macroporous SB powder, modified kaolin and zirconium oxide, the pore volume of the macroporous SB powder is not less than 1 mL / g, and the modified kaolin is prepared according to a process comprising the following steps: the kaolin raw material is once calcined at 500°C to 700°C, then acid-modified, then washed to neutrality, and then calcined twice at 500°C to 600°C to obtain the modified kaolin; the first metal component comprises zinc and nickel, the second metal component comprises potassium and / or magnesium, and the third metal component comprises palladium.

[0007] According to one embodiment of the present invention, based on the oxide of the first metal component, the oxide of the second metal component and the oxide of the third metal, the following conditions are satisfied: the mass of the first metal component accounts for 40% to 70% of the sum of the masses of the carrier and the first metal component; and / or the mass of nickel in the first metal component accounts for 2% to 10% of the sum of the masses of the carrier and the first metal component; and / or the mass of the second metal component accounts for 0.1% to 5% of the sum of the masses of the carrier and the first metal component; and / or the mass of the third metal component accounts for 0.1% to 1% of the sum of the masses of the carrier and the first metal component.

[0008] According to one embodiment of the present invention, the mass ratio of the macroporous SB powder to the modified kaolin is 1:(1-4); and / or, the mass ratio of the zirconium oxide to the macroporous SB powder is (0.5-1.5):1; and / or, the pore volume of the macroporous SB powder is 1.0 mL / g-1.2 mL / g, and the specific surface area is 280 m 2 / g~360m 2 / g, the peptization index is greater than 97%.

[0009] According to one embodiment of the present invention, the time of the first calcination is 3h to 10h; and / or, the temperature of the first calcination is 550℃ to 650℃; and / or, the process of acid modification includes: immersing the kaolin raw material in a first inorganic acid solution for modification, the mass concentration of the first inorganic acid solution is 5% to 20%, and the mass ratio of the first inorganic acid solution to the kaolin raw material is (2 to 7):1; the time of the acid modification is 1h to 6h; and / or, the time of the secondary calcination is 2h to 5h.

[0010] In another aspect of the present invention, a method for preparing the above-mentioned adsorptive desulfurization catalyst is provided, comprising: (I) adding a second inorganic acid and water to a mixture containing the macroporous SB powder, modified kaolin, zirconium oxide, a binder and zinc oxide, and then sequentially performing molding, drying and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, and drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain a third intermediate; (IV) impregnating the third intermediate with a third impregnation solution containing a compound of a third metal component, and drying and calcining the impregnation product to obtain a catalyst precursor; (V) subjecting the catalyst precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain the adsorptive desulfurization catalyst.

[0011] According to one embodiment of the present invention, the binder comprises at least one of sodium methyl cellulose, sodium carboxymethyl cellulose, sodium carboxymethyl starch, and sesbania powder; and / or, the mass of the nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 0.5% to 5% of the sum of the mass of the macroporous SB powder, modified kaolin, zirconium oxide, zinc oxide and the nickel compound; and / or, the mass ratio of the second inorganic acid to the macroporous SB powder is (0.5 to 1): 1; and / or, the zinc oxide comprises nano zinc oxide powder having a particle size of not more than 100 nm; and / or, the baking step in step (I) The calcination conditions are: calcination temperature of 400°C to 700°C, and calcination time of 1h to 10h; and / or, the calcination conditions in step (II) are: calcination temperature of 400°C to 700°C, and calcination time of 1h to 10h; and / or, the calcination conditions in step (III) are: calcination temperature of 400°C to 700°C, and calcination time of 1h to 10h; and / or, the calcination conditions in step (IV) are: calcination temperature of 400°C to 700°C, and calcination time of 1h to 10h; and / or, in step (V), the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, and the time of the first reduction treatment is 1h to 6h.

[0012] In another aspect of the present invention, a method for desulfurization of sulfur-containing oil is provided, comprising: using the above-mentioned adsorption desulfurization catalyst to desulfurize the sulfur-containing oil; or, preparing the adsorption desulfurization catalyst according to the above-mentioned preparation method, and using the prepared adsorption desulfurization catalyst to desulfurize the sulfur-containing oil.

[0013] According to one embodiment of the present invention, the temperature of the desulfurization treatment is 300°C to 550°C; and / or, the pressure of the desulfurization treatment is 0.5MPa to 10MPa; and / or, the feed space velocity of the sulfur-containing oil product is 0.1h -1 ~1.0h -1 ; and / or, the desulfurization treatment is carried out under a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):1.

[0014] According to one embodiment of the present invention, the method further comprises: obtaining a desulfurized oil product and a regenerated catalyst after the desulfurization treatment; regenerating the regenerated catalyst to obtain a regenerated catalyst; and returning the regenerated catalyst to the desulfurization treatment; wherein the regeneration treatment comprises: subjecting the regenerated catalyst to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000 h / min. -1 ~3000h -1 The temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5 MPa, and the time of the oxidation regeneration is 20h to 100h; the regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated catalyst; wherein the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300° C. to 500° C., the pressure of the second reduction treatment is 0 to 3 MPa, and the time of the second reduction treatment is 1 h to 6 h.

[0015] According to one embodiment of the present invention, the sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0016] The adsorption desulfurization catalyst provided by the present invention has the advantages of good mechanical properties, long service life, good desulfurization activity, etc., can significantly improve the desulfurization rate, and has a wide range of applications, especially suitable for the desulfurization treatment of heavy oil, effectively removes sulfides such as thiophenes, and realizes the deep desulfurization of sulfur-containing oil products such as heavy oil. At the same time, it can also reduce the viscosity of the oil products and improve the quality of the oil products after desulfurization. The oil products after desulfurization can be used as clean gasoline blending components or other purposes. Studies have shown that the fracture strength of the adsorption desulfurization catalyst is as high as 25N or more, showing good mechanical properties, good structural stability, and is easy to use; the desulfurization rate of heavy oil is as high as more than 90%, or even more than 92%, and the adsorption desulfurization catalyst can still achieve a good desulfurization rate after regeneration 1 to 60 times or even more times, showing good activity stability and long service life. In addition, the raw materials of the adsorption desulfurization catalyst of the present invention are cheap and easy to obtain, and it also has the advantages of low cost, simple preparation process, and simple desulfurization process using the adsorption desulfurization catalyst, mild conditions, and high efficiency, which is of great significance for practical industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD spectra of catalyst precursors during the preparation of fresh adsorption desulfurization catalysts S1, S2, D4, and D5 (the abscissa is the 2θ angle (Theta), and the ordinate is the peak intensity (intensity));

[0018] Figure 2 This is the XRD spectrum of the regenerated catalyst precursor during the regeneration process of the spent catalyst produced after desulfurization treatment of S1, S2, D4, and D5. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only descriptions of the principles and features of the present invention. The examples cited are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In the description of the present invention, the terms "first", "second", "third", etc. are only used for descriptive purposes, such as distinguishing between components, etc., to more clearly illustrate / explain the technical scheme, and cannot be understood as indicating or implying the number of the indicated technical features or the order of substantial significance.

[0020] The adsorption desulfurization catalyst of the present invention comprises: a carrier, a first metal component, a second metal component and a third metal component; wherein the carrier is compounded from raw materials containing macroporous SB powder, modified kaolin and zirconium oxide, the pore volume of the macroporous SB powder is not less than 1 mL / g, and the modified kaolin is prepared according to a process comprising the following steps: the kaolin raw material is once calcined at 500°C to 700°C, then acid-modified, then washed to neutrality, and then calcined twice at 500°C to 600°C to obtain the modified kaolin; the first metal component comprises zinc and nickel, the second metal component comprises potassium and / or magnesium, and the third metal component comprises palladium.

[0021] The inventors have studied and analyzed that, in the composition system of the adsorption desulfurization catalyst of the present invention, the first metal component serves as the main active component for sulfur adsorption / absorption. In the desulfurization treatment process of the oil product, the third metal component can activate the CS bond of the sulfide in the oil product, improve the CS reaction activity, and make the sulfur element therein be captured by the nickel component to form nickel sulfide. The nickel sulfide reacts with the zinc component to form zinc sulfide. The second metal component, as an active metal, can promote the sulfur transfer and other processes. Thus, through multi-step coordinated reactions, the sulfur component in the oil product is adsorbed in the adsorption desulfurization catalyst in the form of metal sulfides such as zinc sulfide, thereby achieving the purpose of desulfurization.

[0022] Generally speaking, when using conventional alumina-based carriers and adsorption desulfurization catalysts with zinc oxide and nickel as the main adsorption active components for adsorption desulfurization of heavy oil, there will be at least the following two problems: first, the desulfurization efficiency is low, and the sulfur content in the desulfurized oil obtained after desulfurization is still high; second, there is a strong interaction between the adsorption active components (such as ZnO) and the carrier Al2O3, and zinc-aluminum spinel is easily formed during the adsorption desulfurization reaction, catalyst regeneration and other cyclic processes, causing some adsorption active components such as ZnO to lose the ability to desulfurize and store sulfur, thereby gradually deactivating the adsorption desulfurization catalyst, and also reducing the strength of the catalyst, affecting the desulfurization performance and service life of the catalyst.

[0023] According to the research of the present invention, the above-mentioned carrier composed of macroporous SB powder, modified kaolin and zirconium oxide is used to match the above-mentioned first metal component, second metal component and third metal component to form an adsorption desulfurization catalyst, which can effectively solve the above-mentioned problems. The inventor believes through research and analysis that in the preparation process of modified kaolin, after roasting and acid modification, on the one hand, the groups in the inner layer of the original kaolin crystal are exposed, the types and number of its surface active points are increased, the cracking activity is improved, the viscosity of the heavy oil feedstock can be reduced, and it is beneficial to improve the desulfurization activity of the catalyst. On the other hand, the acid modification process extracts part of the active aluminum atoms in the kaolin, increases the pore volume of the kaolin (such as using kaolin with a pore volume of 0.1mL / g). When the raw material is used, after the above-mentioned roasting and acid modification, the pore volume can be increased from 0.1mL / g to 0.6mL / g). The larger pore volume is beneficial to the desulfurization activity of the catalyst. At the same time, after the active aluminum in the kaolin is removed by acid extraction, the remaining aluminum and silicon form a stable structure, which can also reduce the probability of aluminum in the kaolin and zinc oxide producing zinc aluminum spinel, thereby ensuring the stability of the adsorption desulfurization catalyst; the addition of zirconium oxide in the carrier can improve the dispersion of the active components of the catalyst, weaken the interaction between aluminum oxide and zinc oxide, and further inhibit the formation of zinc aluminum spinel, especially inhibit the formation of zinc aluminum spinel during the catalyst reaction regeneration process, thereby further ensuring the stability of the catalyst, facilitating its recycling and regeneration, and increasing its service life.

[0024] For example, the primary calcination temperature may be 500° C., 550° C., 600° C., 650° C., 700° C., or any two thereof. In addition, the primary calcination time may be 3 h to 10 h, such as 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, or any two thereof, preferably 5 h to 7 h.

[0025] In the preparation process of the modified kaolin, a first inorganic acid may be used for acid modification. Preferably, the first inorganic acid includes nitric acid (HNO 3 ). In some embodiments, the acid modification process includes: soaking the kaolin raw material in a first inorganic acid solution for acid modification, the mass concentration of the first inorganic acid solution is 5% to 20%, for example, 5%, 8%, 10%, 12%, 15%, 18%, 20% or any two thereof, preferably 10% to 15%; the mass ratio of the first inorganic acid solution to the kaolin raw material is (2 to 7):1, for example, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1 or any two thereof, preferably (3 to 5):1, the first inorganic acid solution is, for example, a nitric acid solution with a mass concentration of 5% to 20% (its mass concentration is the mass ratio of the HNO3 solute therein to the total mass of the nitric acid solution composed of HNO3 solute and water (solvent)). In addition, the acid modification time may generally be 1 h to 6 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h or a range consisting of any two thereof, preferably 3 h to 4 h.

[0026] In the process of preparing modified kaolin, after acid modification, the obtained acid-modified product can be repeatedly filtered and washed until it is washed to neutrality, and then subjected to secondary calcination. The time of the secondary calcination can generally be 2h to 5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or a range consisting of any two thereof. Exemplarily, the temperature of the secondary calcination can be 500°C, 520°C, 540°C, 560°C, 580°C, 600°C or a range consisting of any two thereof.

[0027] In the present invention, the carrier is compounded by macroporous SB powder, modified kaolin and zirconium oxide. To further optimize the catalyst performance, the pore volume of the macroporous SB powder can be 1.0 mL / g to 1.2 mL / g, such as 1 mL / g, 1.1 mL / g, 1.2 mL / g, etc. The specific surface area of ​​the macroporous SB powder can be 280 m 2 / g~360m 2 / g, for example 280m 2 / g、300m 2 / g, 320m 2 / g, 340m 2 / g, 350m 2 / g, 360m 2 / g or any two of them, the peptization index of the macroporous SB powder is greater than 97%.

[0028] In addition, the mass ratio of the macroporous SB powder to the modified kaolin can be 1:(1-4), such as 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4 or any two thereof. The mass ratio of zirconium oxide to the macroporous SB powder can be (0.5-1.5):1, such as 0.5:1, 0.7:1, 1:1, 1.2:1, 1.5:1 or any two thereof.

[0029] In the above-mentioned adsorption desulfurization catalyst, the mass percentage of the first metal component serving as the sulfur absorption unit is generally not lower than (i.e. equal to or greater than) the mass percentage of the carrier. In some preferred embodiments, the mass of the first metal component, calculated as the oxide of the first metal component, accounts for 40% to 70% of the sum of the masses of the carrier and the first metal component, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70% or the range consisting of any two thereof, and the mass of the carrier accounts for 30% to 65% of the sum of the masses of the carrier and the first metal component, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or the range consisting of any two thereof.

[0030] In general, the mass percentage of zinc in the first metal component is preferably higher than the mass percentage of nickel, calculated as the oxide of the first metal component. In some embodiments, the mass of nickel in the first metal component accounts for 2% to 10% of the sum of the mass of the support and the first metal component, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two thereof, calculated as the oxide of the first metal component.

[0031] In addition, in some embodiments, the mass of the second metal component, calculated as the oxide of the first metal component and the oxide of the second metal component, accounts for 0.1% to 5% of the sum of the masses of the carrier and the first metal component, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of them.

[0032] In some embodiments, the mass of the third metal component, calculated as the oxide of the first metal component and the oxide of the third metal component, accounts for 0.1% to 1% of the sum of the masses of the support and the first metal component, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two thereof.

[0033] In the above-mentioned adsorptive desulfurization catalyst, the first metal component, the second metal component and the third metal component are loaded on a carrier. Generally, most of the metal components exist in the form of oxides (such as zinc exists in the form of zinc oxide), wherein at least part of the nickel can be present in a reduced state (i.e., in the form of nickel element). In specific implementation, compounds of each metal component (such as metal oxides and / or metal salts, etc.) can be used to load each metal component on a carrier by an impregnation method. After the loading of each metal component is completed, the obtained catalyst precursor is subjected to a first reduction treatment in an atmosphere containing hydrogen, so that the nickel component therein is at least partially reduced to nickel element, thereby obtaining an adsorptive desulfurization catalyst and improving its desulfurization activity.

[0034] The above-mentioned carrier can be specifically prepared by compounding raw materials containing macroporous SB powder, modified kaolin, zirconium oxide and a binder, and its preparation process can include: mixing macroporous SB powder, modified kaolin, zirconium oxide, a binder with an inorganic acid and water, and then drying and calcining to form a carrier. The metal component can be introduced during the preparation of the carrier, or the metal component can be impregnated after the carrier is prepared.

[0035] In a preferred embodiment of the present invention, the preparation method of the above-mentioned adsorption desulfurization catalyst comprises: (I) adding a second inorganic acid and water to a mixture containing macroporous SB powder, modified kaolin, zirconium oxide, a binder and zinc oxide, and then sequentially forming, drying and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, drying and calcining the impregnation product to obtain a third intermediate; (IV) impregnating the third intermediate with a third impregnation solution containing a compound of a third metal component, drying and calcining the impregnation product to obtain a catalyst precursor; (V) subjecting the catalyst precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain an adsorption desulfurization catalyst.

[0036] In the above preparation process, zinc oxide, a binder and macroporous SB powder, modified kaolin, zirconium oxide and other carrier raw materials are first mixed and formed, and then the nickel compound, the second metal component and the third metal component are sequentially impregnated by an impregnation method, which can improve the strength and desulfurization activity of the prepared adsorption desulfurization catalyst. The inventor believes through research and analysis that in the above preparation process, after the drying and calcination treatments of steps (I) to (IV), macroporous SB powder, modified kaolin and zirconium oxide are compounded to form a carrier, and the binder gradually volatilizes during the calcination process, thereby forming a pore structure in the prepared catalyst, and the compounds of each metal component are basically converted into metal oxides; after the first reduction treatment of step (V), the nickel therein can be basically present in a reduced state, while other metal components (such as zinc, the second metal component and the third metal component) are usually still present in the form of metal oxides, thereby preparing an adsorption desulfurization catalyst with suitable composition and structure, which is suitable for the desulfurization treatment of heavy oil, and can show good adsorption desulfurization activity, stability and mechanical properties, and improve the desulfurization rate and service life.

[0037] Specifically, in the above preparation process, the first metal component compound includes zinc oxide and nickel compound, the second metal component compound includes potassium compound and / or magnesium compound, and the third metal component compound includes palladium compound. In general, the content of each metal component in the prepared catalyst can be regulated by the amount of raw materials such as each metal component compound, and the amount of each raw material is as follows: based on the oxide of each metal component (such as nickel compound based on nickel oxide, potassium compound based on potassium oxide, magnesium compound based on magnesium oxide, and palladium compound based on palladium oxide), the mass of the first metal component compound accounts for 40% to 70% of the sum of the mass of the carrier and the first metal component compound, the mass of the nickel compound accounts for 2% to 10% of the sum of the mass of the carrier and the first metal component compound, the mass of the second metal component compound accounts for 0.1% to 5% of the sum of the mass of the carrier and the first metal component compound, the mass of the third metal component compound accounts for 0.1% to 1% of the sum of the mass of the carrier and the first metal component compound, the mass ratio of macroporous SB powder to modified kaolin is 1: (1 to 4), and the mass ratio of zirconium oxide to macroporous SB powder is (0.5 to 1.5): 1.

[0038] In step (I), the mixture can be a wet mixture, a paste mixture, a kneaded body or a slurry, etc., and the molding process can be oil-ammonia column molding, oil-water column molding, oil column molding, rolling ball molding or extrusion ball molding, etc., preferably extrusion ball molding, wherein the amount of water used can be convenient for molding, for example, it can meet the extrusion ball molding, and there is no particular restriction on this. Through the above molding process, the first intermediate formed can be spherical and / or toothed ball-shaped, and the particle diameter of the first intermediate is preferably 1.5mm to 3mm, for example, 1.5mm, 2mm, 2.5mm, 3mm or the range composed of any two thereof.

[0039] In step (I), the zinc oxide may include nano-sized particles of zinc oxide, preferably nano zinc oxide powder with a particle size of no more than 100 nm. In specific implementation, the purity of the zinc oxide used is greater than 96%.

[0040] In step (I), the binder may include at least one of sodium methyl cellulose, sodium carboxymethyl cellulose, sodium carboxymethyl starch, and sesbania powder. In addition, the amount of the binder can generally be controlled as follows: the mass of the nickel compound in step (II) is calculated as nickel oxide, and the mass of the binder accounts for 0.5% to 5% of the sum of the mass of the macroporous SB powder, modified kaolin, zirconium oxide, zinc oxide and the nickel compound, for example, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of them.

[0041] In some embodiments, in step (I), the mass ratio of the second inorganic acid to the macroporous SB powder is (0.5-1):1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1 or any two thereof. It should be noted that the mass ratio of the second inorganic acid to the macroporous SB powder is calculated based on the second inorganic acid without solvents such as water. In specific implementation, second inorganic acid solutions of different concentrations may be used. The mass of the second inorganic acid therein can be converted according to its concentration to control the mass ratio of the second inorganic acid (non-solution) to the macroporous SB powder to be (0.5-1):1. Preferably, the inorganic acid comprises nitric acid.

[0042] In step (II), the first impregnation solution may be a solution or suspension containing a nickel compound, and the nickel compound may particularly include a soluble nickel compound (generally a water-soluble compound). The first impregnation solution is a solution prepared by dissolving a soluble nickel compound in water. The soluble nickel compound may include, for example, a soluble nickel salt, preferably nickel nitrate and / or nickel acetate. The soluble nickel salt may be in the form of a hydrate without or with water of crystallization, and the present invention is not particularly limited to this.

[0043] In specific implementation, in step (II), the impregnation can be carried out by an equal volume impregnation method. In some specific embodiments, in step (II), the impregnation temperature is 20°C to 90°C, such as 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or any two thereof in the range, preferably 40 to 65°C, the impregnation time is 1h to 24h, such as 1h, 5h, 10h, 15h, 20h, 24h or any two thereof in the range, preferably 6h to 12h; the mass ratio of the first impregnation liquid to the first intermediate is (2 to 4): 1, such as 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1 or any two thereof in the range.

[0044] In step (III), the second impregnation solution may be a solution or a suspension. Preferably, the compound of the second metal component includes a soluble compound of the second metal component (generally a water-soluble compound). The second impregnation solution is a solution prepared by dissolving the soluble compound of the second metal component in water. The compound of the second metal component may specifically include a soluble salt of the second metal component (i.e., a soluble salt of potassium and / or a soluble salt of magnesium), preferably a nitrate of the second metal component (i.e., potassium nitrate and / or magnesium nitrate).

[0045] In specific implementation, in step (III), the impregnation can be carried out by an equal volume impregnation method. In some embodiments, in step (III), the impregnation temperature is 20°C to 90°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C or any two thereof in the range, preferably 40 to 65°C, the impregnation time is 1h to 24h, for example, 1h, 5h, 10h, 15h, 20h, 24h or any two thereof in the range, preferably 6h to 12h; the mass ratio of the second impregnation liquid to the second intermediate is (2 to 4): 1, for example, 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1 or any two thereof in the range.

[0046] In step (IV), the third impregnation liquid may be a solution or a suspension. Preferably, the compound of the third metal component includes a soluble compound of the third metal component (generally a water-soluble compound). The third impregnation liquid is a solution prepared by dissolving the soluble compound of the third metal component in water. The compound of the third metal component may specifically include a soluble salt of the third metal component, preferably a nitrate, such as palladium nitrate.

[0047] In specific implementation, in step (IV), the impregnation can be carried out by an equal volume impregnation method. In some embodiments, in step (IV), the impregnation temperature is 20°C to 90°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C or any two thereof in the range, preferably 40 to 65°C, and the impregnation time is 1h to 24h, for example, 1h, 5h, 10h, 15h, 20h, 24h or any two thereof in the range, preferably 6h to 12h; the mass ratio of the third impregnation liquid to the third intermediate is (1 to 3): 1, for example, 1: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1, or any two thereof in the range.

[0048] Optionally, the drying process in step (I), step (II), step (III), and step (IV) independently comprises: first drying at 20°C to 30°C (such as room temperature) for 12h to 48h, then drying at 60°C to 120°C (preferably 80°C to 110°C) for 3h to 24h (preferably 6h to 10h), and then calcining the obtained dried product. The drying temperature, drying time and other conditions in step (I), step (II), step (III), and step (IV) may be the same or different.

[0049] In addition, the calcination conditions in step (I), step (II), step (III), and step (IV) can be independently: the calcination temperature is 400°C to 700°C, such as 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, or a range consisting of any two thereof, preferably 450°C to 650°C, and the calcination time is 1h to 10h, such as 1h, 3h, 5h, 7h, 10h, or a range consisting of any two thereof, preferably 3h to 5h. Among them, the calcination temperature, calcination time and other conditions in step (I), step (II), step (III), and step (IV) can be the same or different.

[0050] In step (V), hydrogen can be introduced into the system to contact the catalyst precursor with hydrogen to perform the first reduction treatment. The volume space velocity of hydrogen can be 500h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 、2000h -1 、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, in step (V), the volume fraction of hydrogen in the atmosphere containing hydrogen is 10% to 100%, for example, 10%, 30%, 50%, 60%, 80%, 100% or a range composed of any two thereof, preferably 60% to 100%, and the remainder is, for example, an inert gas.

[0051] In addition, in step (V), the temperature of the first reduction treatment process can be 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof, preferably 350°C to 450°C, the pressure of the first reduction treatment process is 0 to 3MPa, for example, 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or a range consisting of any two thereof, preferably 0.5 to 1.5MPa, and the time of the first reduction treatment is 1h to 6h, for example, 1h, 2h, 3h, 4h, 5h, 6h or a range consisting of any two thereof, preferably 2h to 4h.

[0052] In the present invention, unless otherwise specified, the masses of raw materials such as macroporous SB powder, kaolin, zirconium oxide, zinc oxide, etc. are calculated on a dry basis.

[0053] In one embodiment of the present invention, a method for desulfurization of sulfur-containing oil products is provided, comprising: using the above-mentioned adsorption desulfurization catalyst to desulfurize the sulfur-containing oil products; or, preparing the adsorption desulfurization catalyst according to the above-mentioned preparation method, and using the prepared adsorption desulfurization catalyst to desulfurize the sulfur-containing oil products.

[0054] In some embodiments, the temperature of the desulfurization treatment can be 300°C to 550°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or a range consisting of any two thereof, preferably 400-450°C; the pressure of the desulfurization treatment is 0.5MPa to 10MPa, for example, 0.5MPa, 1MPa, 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa or a range consisting of any two thereof, preferably 3MPa to 7MPa; the feed space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 , for example 0.1h -1 、0.3h -1 、0.5h -1 , 0.8h -1 , 1h -1 Or a range consisting of any two of them.

[0055] In some embodiments, the desulfurization treatment is carried out in a hydrogen atmosphere, that is, the sulfur-containing oil and the adsorption desulfurization catalyst are contacted and reacted in a hydrogen atmosphere to carry out the desulfurization treatment. The volume ratio of hydrogen to the sulfur-containing oil (hydrogen-to-oil volume ratio) is (100-800):1, for example, 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1 or a range consisting of any two of them.

[0056] In some embodiments, the above desulfurization process further includes: obtaining a desulfurized oil product and a regenerated catalyst after desulfurization treatment; regenerating the regenerated catalyst to obtain a regenerated catalyst; and returning the regenerated catalyst for desulfurization treatment.

[0057] The regeneration treatment comprises: subjecting the catalyst to be regenerated to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two thereof, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , for example 1000h -1 、1300h -1 、1500h -1 , 1800h -1 、2000h -1 , 2300h -1 、2500h -1 、2800h -1 、3000h -1 or a range consisting of any two thereof; the temperature of the oxidative regeneration is 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof; the pressure of the oxidative regeneration is 0 to 0.5 MPa; the time of the oxidative regeneration is 20h to 100h; the regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated catalyst; wherein the temperature of the second reduction treatment ... 0℃, 450℃, 500℃ or any two of them in the range, preferably 350~450℃, the pressure of the second reduction treatment is 0~3MPa, for example 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or any two of them in the range, preferably 0.5~1.5MPa, the time of the second reduction treatment is 1h~6h, for example 1h, 2h, 3h, 4h, 5h, 6h or any two of them in the range, preferably 2h~4h. In the present invention, unless otherwise specified, the pressures are all gauge pressures.

[0058] In a specific implementation, hydrogen can be introduced into the system to contact the regenerated catalyst precursor with hydrogen to perform the second reduction treatment. The volume space velocity of hydrogen can be 500 h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 、2000h -1、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, during the second reduction treatment, the volume fraction of hydrogen in the hydrogen-containing atmosphere is 10% to 100%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% or any two thereof, preferably 60% to 100%, and the remainder may be an inert gas or oil gas such as methane.

[0059] Specifically, the above desulfurization treatment is carried out in a reactor, and the reactor may include a fixed bed reactor and / or a moving bed reactor. Taking the fixed bed reactor as an example, in specific implementation, the adsorption desulfurization catalyst may be loaded in the fixed bed reactor, and then the sulfur-containing oil product enters the fixed bed reactor, and contacts and reacts with the adsorption desulfurization catalyst therein to obtain the desulfurized oil product and the regenerated catalyst respectively; after the regenerated catalyst is subjected to the above regeneration treatment, it is returned to the fixed bed reactor to form a cycle.

[0060] In the present invention, the above-mentioned adsorption desulfurization catalyst can be used to remove small molecular sulfides and macromolecular sulfides in sulfur-containing oil products, and has a wide range of applications. Generally, the sulfides in the above-mentioned sulfur-containing oil products include at least one of carbon oxysulfide, carbon disulfide, mercaptan, hydrogen sulfide, and thiophene compounds, but are not limited thereto. For example, thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene. The present invention can efficiently remove these sulfides in sulfur-containing oil products, especially macromolecular sulfides such as thiophenes, achieve deep desulfurization of sulfur-containing oil products, and reduce the total sulfur content of desulfurized oil products. In some specific embodiments, the above-mentioned sulfur-containing oil products include heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0061] Generally speaking, the equivalent double bond value (DBE) of sulfides in heavy oil is distributed between 9 and 16. 22 -C 46 , mainly large molecular sulfides such as benzothiophene, dibenzothiophene, and benzonaphthothiophene, which are difficult to remove, and the asphaltene and colloid particles in the heavy oil are large, which can easily block the catalyst pores and cause catalyst deactivation and other problems. The adsorption desulfurization catalyst of the present invention can efficiently remove sulfides in heavy oil, has good activity and stability, can be regenerated and used multiple times, and maintain good desulfurization efficiency.

[0062] In the present invention, the above-mentioned adsorption desulfurization catalyst is used to desulfurize sulfur-containing oil products, which can improve the desulfurization efficiency, and at the same time reduce the viscosity of the desulfurized oil products, thereby improving the overall quality of the desulfurized oil products. The present invention can also achieve efficient desulfurization and viscosity reduction for heavy oil with high sulfur content and high viscosity, with a sulfur content of about 3.6wt% and a kinematic viscosity of 628mm 2 Taking heavy oil (such as vacuum residue) with a capacity of about 1000 g / s as an example, the above desulfurization process can achieve a desulfurization rate of more than 90% and a kinematic viscosity of 200 mm 2 / s~250mm 2 / s.

[0063] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0064] In the following embodiments, the relevant performance testing process is as follows:

[0065] (1) With reference to the standard "SH / T 0689-2000", the total sulfur content in the liquid oil sample was determined by ultraviolet fluorescence / chemiluminescence method using the American photonLAB total sulfur and total nitrogen analyzer at a temperature of 1000°C, argon gas of 30psi, and oxygen of 10psi. According to this method, the mass percentage of total sulfur in the heavy oil feedstock x0 and the mass percentage of total sulfur in the desulfurized oil product x1 were determined respectively, and the desulfurization rate w was calculated according to w=(x0-x1) / x0;

[0066] (2) A universal automatic strength tester is used to measure the mechanical strength of the molded particles (such as S1 to S6, D1 to D6 below). The instrument range is 0 to 500 N, and the accuracy is 0.1 N. The measurement process is as follows: a single sample is placed between two rigid platforms, one of which remains stationary and the other moves axially downward at a very low speed to produce extrusion friction on the particles. The fracture strength (or crushing strength) is determined as the maximum load measured before the particles break. According to this process, 50 regular particles are selected for each sample to perform a crushing strength test, so as to obtain representative mechanical properties.

[0067] (3) With reference to the standard GB / T 265-1988 Determination of kinematic viscosity and calculation of dynamic viscosity of petroleum products, the time for a certain volume of liquid (such as the heavy oil feedstock and desulfurized oil product described below) to flow through a calibrated glass capillary viscometer under gravity is measured at a constant temperature of 40°C. The kinematic viscosity of the liquid at this temperature is determined by multiplying the capillary constant of the viscometer by the movement time. According to this process, each liquid sample is measured twice, and the average value is taken to obtain the liquid viscosity.

[0068] (4) The crystal structure of each catalyst sample was characterized by X-ray diffraction (XRD) analysis. Specifically, the XRD analysis was performed using a Rigaku D / max 2200PC X-ray powder diffractometer with a Cu target, a graphite monochromator, a scanning speed of 10 degrees / min, a scanning step of 0.02 degrees, a voltage of 40 kV, and a current of 20 mA. The intensity and position of the diffraction peaks in the measured XRD spectrum were used to perform a qualitative analysis to determine the catalyst composition (including the type of substance, structure, crystalline state, and state of element existence, etc.).

[0069] In the following examples and comparative examples, the macroporous SB powder was purchased from Zibo Shuoren Alumina Technology Co., Ltd., model PG-03, with a pore volume of 1.12 mL / g and a specific surface area of ​​336 m 2 / g, the peptization index is greater than 97%. Kaolin was purchased from Suzhou Huashan Kaolin Co., Ltd.; other reagents were purchased from Aladdin Reagent Network; the zinc oxide used was nano zinc oxide powder with a particle size of no more than 100nm.

[0070] Example 1

[0071] (1) 500 g of kaolin was calcined at 700° C. for 6 h; then modified in 2000 g of 12 wt % nitric acid solution for 3 h, filtered and washed until neutral; then calcined at 500° C. for 3 h to obtain modified kaolin;

[0072] (2) 100 g of macroporous SB powder, 100 g of modified kaolin, 100 g of zirconium oxide, 50 g of sesbania powder and 600 g of zinc oxide powder were mixed evenly, 450 g of water and 100 g of nitric acid were added, and after mixing evenly, the mixture was squeezed into small balls with a particle diameter of 2 mm (i.e., formed), and the small balls were naturally dried at room temperature for 24 h; then dried at 100° C. for 8 h; and then calcined at 550° C. for 4 h to obtain a first intermediate in the form of small balls;

[0073] (3) Weigh 389 g of nickel nitrate hexahydrate, add 1700 g of water to it to prepare a first impregnation solution, place the first intermediate in the first impregnation solution, and impregnate at 50° C. for 8 h; then naturally dry at room temperature for 24 h; then dry at 80° C. for 10 h; and then calcine at 500° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0074] (4) Weigh 42.9 g of potassium nitrate, add 2000 g of water to prepare a second impregnation solution, place the second intermediate in the second impregnation solution, and impregnate at 60° C. for 6 h; then naturally dry at room temperature for 12 h; then dry at 110° C. for 6 h; and then calcine at 600° C. for 3 h to obtain a third intermediate in the form of a small sphere;

[0075] (5) Weighing 1.88 g of palladium nitrate, adding 1000 g of water thereto to prepare a third impregnation solution, placing the third intermediate in the third impregnation solution, and impregnating at 60° C. for 6 h; then naturally drying at room temperature for 12 h; then drying at 110° C. for 6 h; and then calcining at 600° C. for 3 h to obtain a spherical catalyst precursor;

[0076] (6) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S1; wherein the reduction treatment conditions are: pressure 1 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 2000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 80%;

[0077] Among them, the first metal component (zinc + nickel), the second metal component (potassium), and the third metal component (palladium) are all calculated as metal oxides. The mass of the first metal component accounts for 70% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 10% of the sum of the masses of the carrier and the first metal component, the mass of the second metal component (potassium oxide) accounts for 4% of the sum of the masses of the carrier and the first metal component, and the mass of the third metal component (palladium oxide) accounts for 0.1% of the sum of the masses of the carrier and the first metal component.

[0078] Example 2

[0079] (1) 500 g of kaolin was calcined at 500° C. for 5 h; then modified in 1600 g of 13 wt % nitric acid solution for 4 h, filtered and washed until neutral; then calcined at 550° C. for 5 h to obtain modified kaolin;

[0080] (2) 104 g of macroporous SB powder, 412 g of modified kaolin, 84 g of zirconium oxide, 10 g of sesbania powder and 500 g of zinc oxide powder were mixed evenly, 480 g of water and 52 g of nitric acid were added, and the mixture was squeezed into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 20 h; then dried at 90° C. for 6 h; and then calcined at 650° C. for 3 h to obtain a first intermediate in the form of small balls;

[0081] (3) Weigh 100 g of nickel acetate tetrahydrate, add 3900 g of water thereto to prepare a first impregnation solution, place the first intermediate in the first impregnation solution, and impregnate at 40° C. for 12 h; then naturally dry at room temperature for 36 h; then dry at 100° C. for 8 h; and then calcine at 450° C. for 5 h to obtain a second intermediate in the form of a small sphere;

[0082] (4) Weigh 18.4 g of magnesium nitrate, add 3900 g of water to prepare a second impregnation solution, place the second intermediate in the second impregnation solution, and impregnate at 55° C. for 8 h; then naturally dry at room temperature for 24 h; then dry at 80° C. for 10 h; and then calcine at 500° C. for 4 h to obtain a third intermediate in the form of a small sphere;

[0083] (5) Weighing 18.8 g of palladium nitrate, adding 2900 g of water thereto to prepare a third impregnation solution, placing the third intermediate in the third impregnation solution, and impregnating at 65° C. for 10 h; then naturally drying at room temperature for 18 h; then drying at 100° C. for 10 h; and then calcining at 650° C. for 3 h to obtain a spherical catalyst precursor;

[0084] (6) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S2; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 400° C., reduction treatment time 4 h, hydrogen volume space velocity 1500 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 70%;

[0085] Among them, the first metal component (zinc + nickel), the second metal component (magnesium), and the third metal component (palladium) are all calculated as metal oxides. The mass of the first metal component accounts for 46.9% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 2.65% of the sum of the masses of the carrier and the first metal component, the mass of the second metal component (magnesium oxide) accounts for 0.44% of the sum of the masses of the carrier and the first metal component, and the mass of the third metal component (palladium oxide) accounts for 0.88% of the sum of the masses of the carrier and the first metal component.

[0086] Example 3

[0087] (1) 500 g of kaolin was calcined at 550° C. for 5 h; then modified in 2500 g of 10 wt% nitric acid solution for 4 h, filtered and washed until neutral; then calcined at 600° C. for 5 h to obtain modified kaolin;

[0088] (2) 107 g of macroporous SB powder, 162 g of modified kaolin, 81 g of zirconium oxide, 20 g of sesbania powder and 600 g of zinc oxide powder were mixed evenly, 472 g of water and 64 g of nitric acid were added, and the mixture was squeezed into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 18 h; then dried at 110° C. for 9 h; and then calcined at 500° C. for 3 h to obtain a first intermediate in the form of small balls;

[0089] (3) Weigh 195 g of nickel nitrate hexahydrate, add 2400 g of water to prepare a first impregnation solution, place the first intermediate in the first impregnation solution, and impregnate at 45° C. for 12 h; then naturally dry at room temperature for 24 h; then dry at 90° C. for 6 h; and then calcine at 600° C. for 3 h to obtain a second intermediate in the form of a small sphere;

[0090] (4) Weigh 21.5 g of potassium nitrate, add 3400 g of water to prepare a second impregnation solution, place the second intermediate in the second impregnation solution, and impregnate at 65° C. for 10 h; then naturally dry at room temperature for 24 h; then dry at 100° C. for 10 h; and then calcine at 550° C. for 5 h to obtain a third intermediate in the form of a small ball;

[0091] (5) Weighing 13.2 g of palladium nitrate, adding 2400 g of water thereto to prepare a third impregnation solution, placing the third intermediate in the third impregnation solution, and impregnating at 45° C. for 12 h; then drying naturally at room temperature for 20 h; then drying at 80° C. for 8 h; and then calcining at 550° C. for 4 h to obtain a spherical catalyst precursor;

[0092] (6) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S3; wherein the reduction treatment conditions are: pressure 0.5 MPa, temperature 450° C., reduction treatment time 2 h, hydrogen volume space velocity 3000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 60%;

[0093] Among them, the first metal component (zinc + nickel), the second metal component (potassium), and the third metal component (palladium) are all calculated as metal oxides. The mass of the first metal component accounts for 65% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 5% of the sum of the masses of the carrier and the first metal component, the mass of the second metal component (potassium oxide) accounts for 2% of the sum of the masses of the carrier and the first metal component, and the mass of the third metal component (palladium oxide) accounts for 0.7% of the sum of the masses of the carrier and the first metal component.

[0094] Example 4

[0095] (1) 500 g of kaolin was calcined at 600° C. for 6 h; then modified in 2200 g of 11 wt % nitric acid solution for 3 h, filtered and washed until neutral; then calcined at 550° C. for 4 h to obtain modified kaolin;

[0096] (2) 95 g of macroporous SB powder, 191 g of modified kaolin, 114 g of zirconium oxide, 40 g of sodium methyl cellulose and 520 g of zinc oxide powder were mixed evenly, 510 g of water and 67 g of nitric acid were added, and the mixture was squeezed into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 12 h; then dried at 100° C. for 10 h; and then calcined at 450° C. for 5 h to obtain a first intermediate in the form of small balls;

[0097] (3) Weighing 266 g of nickel acetate tetrahydrate, adding 3600 g of water thereto to prepare a first impregnation solution, placing the first intermediate in the first impregnation solution, and impregnating at 55° C. for 8 h; then drying naturally at room temperature for 24 h; then drying at 80° C. for 10 h; and then calcining at 500° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0098] (4) Weigh 55.2 g of magnesium nitrate, add 2500 g of water to prepare a second impregnation solution, place the second intermediate in the second impregnation solution, and impregnate at 60° C. for 9 h; then naturally dry at room temperature for 18 h; then dry at 110° C. for 6 h; and then calcine at 600° C. for 3 h to obtain a third intermediate in the form of a small sphere;

[0099] (5) Weighing 11.3 g of palladium nitrate, adding 2000 g of water thereto to prepare a third impregnation solution, placing the third intermediate in the third impregnation solution, and impregnating at 40° C. for 12 h; then naturally drying at room temperature for 24 h; then drying at 110° C. for 10 h; and then calcining at 500° C. for 4 h to obtain a spherical catalyst precursor;

[0100] (6) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S4; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 370° C., reduction treatment time 3 h, hydrogen volume space velocity 2000 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 90%;

[0101] Among them, the first metal component (zinc + nickel), the second metal component (magnesium), and the third metal component (palladium) are all calculated as metal oxides. The mass of the first metal component accounts for 60% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 8% of the sum of the masses of the carrier and the first metal component, the mass of the second metal component (magnesium oxide) accounts for 1.5% of the sum of the masses of the carrier and the first metal component, and the mass of the third metal component (palladium oxide) accounts for 0.6% of the sum of the masses of the carrier and the first metal component.

[0102] Example 5

[0103] (1) 500 g of kaolin was calcined at 650° C. for 7 h; then modified in 1800 g of 14 wt% nitric acid solution for 3 h, filtered and washed until neutral; then calcined at 600° C. for 4 h to obtain modified kaolin;

[0104] (2) 92 g of macroporous SB powder, 229 g of modified kaolin, 129 g of zirconium oxide, 30 g of sodium carboxymethyl cellulose and 490 g of zinc oxide powder were mixed evenly, 431 g of water and 74 g of nitric acid were added, the mixture was mixed evenly and then extruded into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 36 h; then dried at 80° C. for 8 h; and then calcined at 450° C. for 3 h to obtain a first intermediate in the form of small balls;

[0105] (3) Weigh 234 g of nickel nitrate hexahydrate, add 2800 g of water to prepare a first impregnation solution, place the first intermediate in the first impregnation solution, and impregnate at 55° C. for 8 h; then naturally dry at room temperature for 20 h; then dry at 110° C. for 8 h; and then calcine at 450° C. for 4 h to obtain a second intermediate in the form of a small sphere;

[0106] (4) Weigh 32.2 g of potassium nitrate, add 2500 g of water to prepare a second impregnation solution, place the second intermediate in the second impregnation solution, and impregnate at 50° C. for 12 h; then naturally dry at room temperature for 24 h; then dry at 110° C. for 10 h; and then calcine at 550° C. for 3 h to obtain a third intermediate in the form of small balls;

[0107] (5) Weigh 9.4 g of palladium nitrate, add 2000 g of water to prepare a third impregnation solution, place the third intermediate in the third impregnation solution, and impregnate at 65° C. for 8 h; then naturally dry at room temperature for 12 h; then dry at 110° C. for 10 h; and then calcine at 650° C. for 3 h to obtain a spherical catalyst precursor;

[0108] (6) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S5; wherein the reduction treatment conditions are: pressure 1 MPa, temperature 400° C., reduction treatment time 3 h, hydrogen volume space velocity 2500 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 100%;

[0109] Among them, the first metal component (zinc + nickel), the second metal component (potassium), and the third metal component (palladium) are all calculated as metal oxides. The mass of the first metal component accounts for 55% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 6% of the sum of the masses of the carrier and the first metal component, the mass of the second metal component (potassium oxide) accounts for 3% of the sum of the masses of the carrier and the first metal component, and the mass of the third metal component (palladium oxide) accounts for 0.5% of the sum of the masses of the carrier and the first metal component.

[0110] Example 6

[0111] (1) 500 g of kaolin was calcined at 600° C. for 5 h; then modified in 1900 g of 15 wt% nitric acid solution for 3 h, filtered and washed until neutral; then calcined at 500° C. for 2 h to obtain modified kaolin;

[0112] (2) 103 g of macroporous SB powder, 205 g of modified kaolin, 92 g of zirconium oxide, 30 g of sesbania powder and 530 g of zinc oxide powder were mixed evenly, 495 g of water and 93 g of nitric acid were added, and the mixture was squeezed into small balls with a particle diameter of 2 mm; the small balls were naturally dried at room temperature for 24 h; then dried at 90° C. for 10 h; and then calcined at 550° C. for 3 h to obtain a first intermediate in the form of small balls;

[0113] (3) Weigh 233 g of nickel acetate tetrahydrate, add 2500 g of water to prepare a first impregnation solution, place the first intermediate in the first impregnation solution, and impregnate at 60° C. for 6 h; then naturally dry at room temperature for 12 h; then dry at 90° C. for 8 h; and then calcine at 500° C. for 3 h to obtain a second intermediate in the form of a small sphere;

[0114] (4) Weigh 36.8 g of magnesium nitrate, add 2500 g of water to prepare a second impregnation solution, place the second intermediate in the second impregnation solution, and impregnate at 65° C. for 10 h; then naturally dry at room temperature for 24 h; then dry at 100° C. for 10 h; and then calcine at 650° C. for 4 h to obtain a third intermediate in the form of small balls;

[0115] (5) Weigh 7.5 g of palladium nitrate, add 1500 g of water to prepare a third impregnation solution, place the third intermediate in the third impregnation solution, and impregnate at 45° C. for 12 h; then naturally dry at room temperature for 36 h; then dry at 80° C. for 8 h; and then calcine at 450° C. for 5 h to obtain a spherical catalyst precursor;

[0116] (6) The catalyst precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical adsorption desulfurization catalyst S6; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 400° C., reduction treatment time 3 h, hydrogen volume space velocity 3000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 80%;

[0117] Among them, the first metal component (zinc + nickel), the second metal component (magnesium), and the third metal component (palladium) are all calculated as metal oxides. The mass of the first metal component accounts for 60% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 7% of the sum of the masses of the carrier and the first metal component, the mass of the second metal component (magnesium oxide) accounts for 1% of the sum of the masses of the carrier and the first metal component, and the mass of the third metal component (palladium oxide) accounts for 0.4% of the sum of the masses of the carrier and the first metal component.

[0118] Comparative Example 1 to Comparative Example 6

[0119] The difference between Comparative Example 1 and Example 3 is that the macroporous SB powder in step (2) is replaced by modified kaolin prepared according to step (1) of Example 3, and the other conditions are the same as those of Example 3 to prepare an adsorption desulfurization catalyst D1.

[0120] The difference between Comparative Example 2 and Example 3 is that the modified kaolin in step (2) is replaced by macroporous SB powder, and the other conditions are the same as those in Example 3 to prepare an adsorption desulfurization catalyst D2.

[0121] The difference between Comparative Example 3 and Example 3 is that the modified kaolin in step (2) is replaced by macroporous pseudo-boehmite (the pore volume of the macroporous pseudo-boehmite is 0.8 mL / g to 1.2 mL / g and the specific surface area is 280 m 2 / g~360m 2 / g), and the other conditions were the same as those in Example 3 to prepare adsorptive desulfurization catalyst D3.

[0122] The difference between Comparative Example 4 and Example 3 is that the zirconium oxide in step (2) is replaced by the modified kaolin prepared according to step (1) of Example 3, and the other conditions are the same as those of Example 3, to prepare the adsorption desulfurization catalyst D4.

[0123] The difference between Comparative Example 5 and Example 4 is that the zirconium oxide in step (2) is replaced by macroporous SB powder, and the other conditions are the same as those in Example 4, to prepare an adsorption desulfurization catalyst D5.

[0124] The difference between Comparative Example 6 and Example 4 is that step (5) is omitted, that is, palladium is not impregnated, and the third intermediate is directly subjected to the reduction treatment of step (6). The other conditions are the same as those of Example 4, and an adsorption desulfurization catalyst D6 is obtained.

[0125] Application Examples

[0126] The desulfurization process of this application example is as follows: 200g of catalyst is loaded into a fixed bed reactor, and then a heavy oil raw material is introduced into the fixed bed reactor, and is contacted and reacted with the adsorption desulfurization catalyst under a hydrogen atmosphere (i.e., a desulfurization reaction is performed), and a desulfurized oil product and a spent catalyst are obtained respectively; wherein the heavy oil raw material is a vacuum residue oil with a sulfur content of 3.6wt% and a viscosity of 628mm 2 / s, the desulfurization process conditions are: temperature 440 ° C, pressure 4MPa, heavy oil feed rate 100g / h (heavy oil feed space velocity 0.6h -1 ), hydrogen flow rate 35L / h (the volume ratio of hydrogen to heavy oil feedstock is 400:1).

[0127] S1-S6 and D1-D6 were used as adsorption desulfurization catalysts to carry out the above desulfurization process, so as to evaluate the performance of S1-S6 and D1-D6. The crushing strength of catalysts S1-S6 and D1-D6, the desulfurization rate achieved by each catalyst, and the viscosity of the desulfurized oil obtained after adsorption desulfurization of heavy oil raw materials by each catalyst are shown in Table 1 and Table 2 respectively.

[0128] Table 1 Catalyst performance evaluation results

[0129] Adsorption desulfurization catalyst S1 S2 S3 S4 S5 S6 Crushing strength / N 28 29 30 27 25 26 Desulfurization rate / % 92 93 94 96 97 95 <![CDATA[Viscosity of desulfurized oil / (mm 2 / s)]]> 230 245 226 217 246 235

[0130] Table 2 Catalyst performance evaluation results

[0131] Adsorption desulfurization catalyst D1 D2 D3 D4 D5 D6 Crushing strength / N 8 18 15 25 23 26 Desulfurization rate / % 93 68 78 93 91 85 <![CDATA[Viscosity of desulfurized oil / (mm 2 / s)]]> 210 530 549 223 289 334

[0132] It can be seen from Table 1 and Table 2 that S1-S6 have good mechanical properties and can improve the desulfurization rate and reduce the viscosity of heavy oil, thereby improving the quality of desulfurized oil products.

[0133] In addition, the catalyst stability of S1~S6 and D1~D6 was evaluated, and the desulfurization activity of the catalyst after different regeneration times was measured. The results showed that the desulfurization activity stability of S1~S6 was much better than that of D1~D6. Specifically, the desulfurization rate of the catalyst after different regeneration times was measured according to the following desulfurization-regeneration process:

[0134] The above desulfurization process is carried out using unused fresh catalyst to obtain desulfurized oil products and once-regenerated catalyst, and the desulfurization rate of the fresh catalyst is measured;

[0135] The regenerated catalyst is regenerated according to the following regeneration process: the regenerated catalyst is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 6%, and the volume space velocity of the oxygen-containing gas is 2000h -1 The temperature of the oxidation regeneration is 450°C, the pressure of the oxidation regeneration is 0.5 MPa, and the time of the oxidation regeneration is 48 h; the regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated catalyst (i.e., regenerated once); wherein the volume fraction of hydrogen in the atmosphere containing hydrogen is 65%, and the volume space velocity of hydrogen is 2500 h -1 , the temperature of the second reduction treatment is 400°C, the pressure of the second reduction treatment is 1.0MPa, and the time of the second reduction treatment is 3h;

[0136] The above desulfurization process is carried out using a once-regenerated catalyst to obtain a desulfurized oil product and a second-time regenerated catalyst, and the desulfurization rate of the once-regenerated catalyst is measured; the second-time regenerated catalyst is then regenerated according to the above regeneration process to obtain a second-time regenerated catalyst (i.e., regenerated twice); the above desulfurization process is carried out using a second-time regenerated catalyst to obtain a desulfurized oil product and a second-time regenerated catalyst, and the desulfurization rate of the second-time regenerated catalyst is measured… According to the above process, the desulfurization rates after the catalyst is regenerated 1 time, 5 times, 10 times, 15 times, 20 times, 25 times, 30 times, 35 times, 40 times, 45 times, 50 times, and 60 times are measured respectively.

[0137] Taking S3, S4, D4 and D5 as examples, the desulfurization rates corresponding to different regeneration times measured according to the above process are shown in Table 3.

[0138] Table 3 Catalyst stability evaluation results

[0139]

[0140] Note: After D4 and D5 were regenerated 15 times, the desulfurization rate dropped significantly and was not shown in Table 3.

[0141] It can be seen from Table 3 that after S3 and S4 were regenerated 60 times, they were still able to maintain a high desulfurization rate, which was basically equivalent to that of the fresh adsorption desulfurization catalyst, showing good desulfurization activity stability.

[0142] In addition, in order to further illustrate the performance difference between the adsorption desulfurization catalyst prepared in the above embodiment and the adsorption desulfurization catalyst prepared in the comparative example, taking S1, S2, D4, and D5 as examples, the catalyst precursor in the preparation process (i.e., the product before the first reduction treatment) and the regenerated catalyst precursor when the fifth regeneration is carried out according to the above desulfurization-regeneration process (i.e., the product before the second reduction treatment) are subjected to XRD analysis, and the results are shown in FIG. Figure 1 and Figure 2 ,in, Figure 1 The fresh agent S1 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst S1, the fresh agent S2 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst S2, the fresh agent D4 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst D4, and the fresh agent D5 is a catalyst precursor in the preparation process of the fresh adsorption desulfurization catalyst D5; Figure 2 The regeneration agent S1 is a regeneration catalyst precursor used in the regeneration process of the catalyst to be regenerated after desulfurization treatment with the fresh adsorption desulfurization catalyst S1 according to the above desulfurization process, the regeneration agent S2 is a regeneration catalyst precursor used when the fresh adsorption desulfurization catalyst S2 is regenerated for the fifth time according to the above desulfurization-regeneration process, the regeneration agent D4 is a regeneration catalyst precursor used when the fresh adsorption desulfurization catalyst D4 is regenerated for the fifth time according to the above desulfurization-regeneration process, and the regeneration agent D5 is a regeneration catalyst precursor used when the fresh adsorption desulfurization catalyst D5 is regenerated for the fifth time according to the above desulfurization-regeneration process.

[0143] from Figure 1 and Figure 2 It can be seen that the main characteristic diffraction peaks in fresh agent S1, fresh agent S2, fresh agent D4 and fresh agent D5 are zinc oxide crystal phase peaks (2θ is 31.5°, 34.4° and 36.2°) and nickel oxide crystal phase peaks (2θ is 36.9° and 43.0°). The characteristic diffraction peak of ZnO is sharp and has high intensity, and it is the main active component. Compared with the fresh agent, the XRD spectra of the regenerated agent (i.e., regenerated agent S1, regenerated agent S2, regenerated agent D4 and regenerated agent D5) are Figure 2 ) is significantly more complex, in which, in addition to regeneration products such as ZnO and NiO, new phases such as desulfurization products ZnS, ZnAl2O4, and Zn2SiO4 are generated. Compared with regeneration agents S1, S2, D4, and D5, the intensities of the characteristic diffraction peaks of zinc aluminum spinel and zinc silicate are significantly enhanced in the XRD spectra.

[0144] The active ZnO in the adsorption desulfurization catalyst continuously reacts with the aluminum source and silicon source in the carrier to generate inactive zinc aluminum spinel and zinc silicate, and the zinc aluminum spinel and zinc silicate can no longer be converted into active ZnO during the regeneration process, indicating that they are difficult to regenerate, thereby forming inactive components, and due to their high content, the content of the active component ZnO in the adsorption desulfurization catalyst will be greatly reduced, thereby leading to problems such as difficulty in sulfur transfer during the adsorption desulfurization process and insufficient sulfur storage capacity of the adsorbent, affecting the desulfurization activity and other properties of the adsorption desulfurization catalyst; at the same time, the generation of zinc aluminum spinel and zinc silicate will also destroy the carrier structure, resulting in a decrease in the strength of the adsorption desulfurization catalyst, making the adsorption desulfurization catalyst more easily broken and deteriorating in performance. Therefore, the above XRD analysis further illustrates that, relative to the adsorption desulfurization catalyst prepared in the comparative example, the adsorption desulfurization catalyst prepared in the embodiment has better desulfurization activity stability and mechanical strength and other properties.

[0145] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An adsorption desulfurization catalyst, characterized in that: It comprises a carrier, a first metal component, a second metal component and a third metal component; wherein, The carrier is compounded from raw materials containing macroporous SB powder, modified kaolin and zirconium oxide, the pore volume of the macroporous SB powder is not less than 1 mL / g, and the modified kaolin is prepared according to a process including the following steps: the kaolin raw material is once calcined at 500°C to 700°C, then acid-modified, then washed to neutrality, and then calcined again at 500°C to 600°C to obtain the modified kaolin, and the acid modification process extracts part of the active aluminum atoms in the kaolin; The first metal component comprises zinc oxide and reduced nickel, the second metal component comprises potassium and / or magnesium, and the third metal component comprises palladium; The preparation steps of the adsorption desulfurization catalyst are as follows: (I) adding a second inorganic acid and water to a mixture containing the macroporous SB powder, modified kaolin, zirconium oxide, a binder and zinc oxide, and then sequentially performing molding, drying and calcining to obtain a first intermediate; (II) impregnating the first intermediate with a first impregnation solution containing a nickel compound, and drying and calcining the impregnation product to obtain a second intermediate; (III) impregnating the second intermediate with a second impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain a third intermediate; (IV) impregnating the third intermediate with a third impregnation solution containing a compound of a third metal component, and drying and calcining the impregnation product to obtain a catalyst precursor; (V) subjecting the catalyst precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain the adsorptive desulfurization catalyst.

2. The adsorption desulfurization catalyst according to claim 1, characterized in that: Calculated based on the oxide of the first metal component, the oxide of the second metal component, and the oxide of the third metal, the following conditions are satisfied: The mass of the first metal component accounts for 40% to 70% of the sum of the mass of the carrier and the first metal component; and / or, The mass of nickel in the first metal component accounts for 2% to 10% of the sum of the mass of the carrier and the first metal component; and / or, The mass of the second metal component accounts for 0.1% to 5% of the sum of the mass of the carrier and the first metal component; and / or, The mass of the third metal component accounts for 0.1% to 1% of the sum of the masses of the carrier and the first metal component.

3. The adsorptive desulfurization catalyst according to claim 1, characterized in that: The mass ratio of the macroporous SB powder to the modified kaolin is 1:(1-4); and / or, The mass ratio of the zirconium oxide to the macroporous SB powder is (0.5-1.5):1; and / or, The pore volume of the macroporous SB powder is 1.0 mL / g to 1.2 mL / g, and the specific surface area is 280 m 2 / g~360m 2 / g, the peptization index is greater than 97%.

4. The adsorptive desulfurization catalyst according to claim 1 or 3, characterized in that: The time of the first calcination is 3h to 10h; and / or, The primary calcination temperature is 550°C to 650°C; and / or, The acid modification process comprises: immersing the kaolin raw material after the first calcination in a first inorganic acid solution for modification, wherein the mass concentration of the first inorganic acid solution is 5% to 20%, and the mass ratio of the first inorganic acid solution to the kaolin raw material is (2 to 7): 1; the acid modification time is 1 hour to 6 hours; and / or, The secondary calcination time is 2h to 5h.

5. The adsorptive desulfurization catalyst according to claim 1, characterized in that: The binder comprises at least one of sodium methyl cellulose, sodium carboxymethyl cellulose, sodium carboxymethyl starch and sesbania powder; and / or, The nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 0.5% to 5% of the sum of the mass of the macroporous SB powder, modified kaolin, zirconium oxide, zinc oxide and the nickel compound; and / or, The mass ratio of the second inorganic acid to the macroporous SB powder is (0.5-1):1; and / or, The zinc oxide comprises nano zinc oxide powder having a particle size not greater than 100 nm; and / or, The calcination conditions in step (I) are: calcination temperature of 400° C. to 700° C., calcination time of 1 h to 10 h; and / or, The calcination conditions in step (II) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, The calcination conditions in step (III) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, The calcination conditions in step (IV) are: calcination temperature of 400°C to 700°C, calcination time of 1h to 10h; and / or, In step (V), the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, the pressure is a gauge pressure, and the time of the first reduction treatment is 1h to 6h.

6. A method for desulfurization of sulfur-containing oil by adsorption, characterized in that: include: The adsorption desulfurization catalyst according to any one of claims 1 to 5 is used to desulfurize sulfur-containing oil products under a hydrogen atmosphere.

7. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: The temperature of the desulfurization treatment is 300°C to 550°C; and / or, The desulfurization treatment pressure is 0.5 MPa to 10 MPa, and the pressure is a gauge pressure; and / or, The feed space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 and / or, The desulfurization treatment is carried out in a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):

1.

8. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: Also includes: After the desulfurization treatment, a desulfurized oil product and a catalyst to be regenerated are obtained respectively; subjecting the catalyst to be regenerated to a regenerated catalyst; The regenerated catalyst is returned to the desulfurization process; wherein the regeneration process comprises: The regenerated catalyst is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated catalyst precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , the temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5MPa, the pressure is gauge pressure, and the time of the oxidation regeneration is 20h to 100h; The regenerated catalyst precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated catalyst; wherein the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300°C to 500°C, the pressure of the second reduction treatment is 0 to 3MPa, the pressure is gauge pressure, and the time of the second reduction treatment is 1h to 6h.

9. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: The sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

Citation Information

Patent Citations

  • Catalytic no-hydroprocessing adsorbing desulfurization for hydrocarbon oil in moving bed reactor

    CN101134908A

  • Combined aluminum oxide-based selective hydrodesulfurization catalyst and preparation method thereof

    CN101439288A

  • Residual oil hydrogenation catalyst and preparation method and use thereof

    CN101491764A

  • Preparation and application methods of adsorption desulfurization agent for upgrading of catalytically cracked gasoline

    CN103642520A

  • Pyrolysis gasoline selective hydrogenation catalyst as well as preparation method and application thereof

    CN104415797A